Dari Jalan Kerajaan Menjadi Jalan Pertokoan Kolonial: Malioboro 1756-1941 - Siti Mahmudah Nur Fauziah (Universitas Gadjah Mada, 2018)
In the colonial period, the beginning of the 20th century became the starting point of the emergence of modern shopping streets in almost all cities in Java, such as Groote Postweg (Postal Highway, now Jalan Ahmad Yani) in Semarang, Bragaweg (Jalan Braga) in Bandung, Jalan Pasar Baru in Weltevreden, Jalan Tunjungan in Surabaya, and Kayutangan (now Jalan Basuki Rahmat) in Malang. In Yogyakarta, Malioboro became the most modern and crowded colonial shopping street at that time. Since the establishment of the Sultanate of Ngayogyakarta Hadiningrat in 1756 Malioboro has played an important role in the palace’s urban planning as a rajamarga (royal road) for certain ceremonies and has become an integral part of the concept of the palace philosophy line which is full of meaning. This paper will describe the development of Malioboro from a royal road into a colonial shopping street in 1756-1941 more comprehensively.The method used in this research is a historical method which includes the selection of topics, collecting resources, verification, interpretation, and writing. As the cornerstone of this research, the data used is relevant data from Gegevens over Djokjakarta’s archives, newspapers, magazines, Rijksblad van Sultanaat Djogjakarta, Kleian’s Adresboek van Geheel Nederlandsch-Indie, Telefoongids voor Java, Madoera en Bali, memoirs, interviews, maps and pictures related to Malioboro.